Model of the supporting leg of an anthropomorphous robot or exoskeleton with two movable links taking into account the dynamics of the electric drive. Power engineering: research, equipment, technology - A. O. Blinov; A. V. Borisov; L. V. Konchina; K. S. Maslova (Известия высших учебных заведений: Проблемы энергетики)
Currently, the direction associated with the development of exoskeletons and anthropomorphic robots is experiencing rapid growth due to the increase in the computing power of microprocessors and the breakthrough development of the theory of control of complex systems, including electromechanical systems that simulate the biomechanics of the human musculoskeletal system. This paper presents a controlled mechatronic robotic model of the support leg of an anthropomorphic robot or exoskeleton with two moving links.GOAL. Mathematical modeling of the dynamics of the supporting leg of an exoskeleton or an anthropomorphic mechanism in the form of two moving links.METHODS. The main difference between the model presented in this study and those created earlier is the use of angles counted between links corresponding to the case of real operation of electric drives. To achieve the goal of the work, the methods of robotics, mathematical modeling, mechatronics, theoretical mechanics, the study of systems of ordinary differential equations, control theory, empirical data for the human musculoskeletal system were applied.RESULTS. For the model of the mechanism, a system of Lagrange equations of the second kind is written, direct and inverse problems of dynamics are solved for a given program control of the motion of a mechatronic robotic system. The results are presented graphically and as an animated visualization of the movement of the links. Calculations were carried out both without taking into account the dynamics of electric drives, and taking into account the rotation of the rotors of electric motors. It has been established that the influence of the dynamics of the rotor of the electric motor on the mechanism is significant.CONCLUSION. The developed methods for setting the program movement of the supporting leg of an exoskeleton or an anthropomorphic robot made it possible to solve direct and inverse problems of dynamics and establish the need to take into account the rotating rotor of an electric motor.